Impact of climate change over distribution and potential range of chestnut in the Iberian Peninsula - Álvarez-Álvarez, Pedro; Aviñoa-Arias, Adrián; Díaz-Varela, Emilio; López-Bao, José Vicente; Pérez-Girón, José Carlos (Frontiers in Forests and Global Change, 2025)
IntroductionThe European chestnut (Castanea sativa Mill.) is a historically and ecologically important tree in the Iberian Peninsula. The species now faces challenges related to the abandonment of traditional management practices, and climate change, although the potential impact of the later on chestnut potential range remains unexplored.MethodsWe assessed variations in chestnut potential range under different climate change scenarios in the Iberian Peninsula, by studying the current and projected habitat suitability of the species across distinct biogeographical regions (Atlantic and Mediterranean) and Regions of Provenance (RoPs). Environmental static (topography and soil parameters) and dynamic (bioclimatic variables) factors were used to build Species Distribution Models (SDMs). Future habitat suitability projections were based on an ensemble of five global circulation models (GCMs) for two climate change scenarios included in CMIP6. The SDMs were constructed using the Random Forest algorithm.Results and DiscussionOur model achieved an accuracy of 86.82%, with high sensitivity (89.91%) and specificity (83.73%). Favourable chestnut habitats were linked to wetter regions, and included factors associated with annual and seasonal precipitations, coldest quarter temperature, soil pH and annual mean temperature. Optimal conditions for chestnut trees include precipitation exceeding 800 mm/year and mean temperature ranging from 10-15°C. Future projections suggest a potential habitat loss for chestnut and slight changes in net primary productivity. The Regions of Provenance exhibit varying levels of resilience, with the Mediterranean regions being particularly vulnerable. We highlight the need to develop mitigation strategies to facilitate chestnut resilience in the face of threats related to climate change.